2017
DOI: 10.1016/j.jaci.2017.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic CD4 + T cells in patients with asthma

Abstract: Asthma encompasses a variety of clinical phenotypes that involve distinct T cell–driven inflammatory processes. Improved understanding of human T-cell biology and the influence of innate cytokines on T-cell responses at the epithelial barrier has led to new asthma paradigms. This review captures recent knowledge on pathogenic CD4+ T cells in asthmatic patients by drawing on observations in mouse models and human disease. In patients with allergic asthma, TH2 cells promote IgE-mediated sensitization, airway hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 195 publications
2
70
0
2
Order By: Relevance
“…In line with the increase in GATA3 and CD4 expression mentioned above, CD4 Th2 cells are known to be key drivers of asthma 17,36 . To assess the presence of Th2 effector cells in the airways of asthma patients (Figure 4G), we single cell sorted CD4 T cells followed by plate-based SmartSeq2 analysis for in depth transcriptional phenotyping of the T helper cell compartment (see Methods for details).…”
Section: Introductionmentioning
confidence: 72%
“…In line with the increase in GATA3 and CD4 expression mentioned above, CD4 Th2 cells are known to be key drivers of asthma 17,36 . To assess the presence of Th2 effector cells in the airways of asthma patients (Figure 4G), we single cell sorted CD4 T cells followed by plate-based SmartSeq2 analysis for in depth transcriptional phenotyping of the T helper cell compartment (see Methods for details).…”
Section: Introductionmentioning
confidence: 72%
“…2 Recent studies have demonstrated that these pro-inflammatory cytokines undermine the structural integrity and impair the epithelial barrier of the respiratory tract. 2 Meanwhile, helminths can induce Tregs to regulate inflammatory responses by releasing anti-inflammatory cytokines, such as IL-10, TGF-β and IL-35. 30 Thus, in the present study, we detected cytokines from the splenocytes and lungs of asthmatic mice.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is an allergic airway inflammation affecting millions of people in the world. CD4 + Th cells, particularly Th2 cells, are traditionally believed as a key player in its pathogenesis . Recently, compelling evidence has demonstrated that Th17 cells are a major contributor to the pathogenesis of allergic airway inflammation, especially severe asthma.…”
Section: Introductionmentioning
confidence: 99%
“…CD4 + Th cells, particularly Th2 cells, are traditionally believed as a key player in its pathogenesis. [17][18][19][20] Recently, compelling evidence has demonstrated that Th17 cells are a major contributor to the pathogenesis of allergic airway inflammation, [21][22][23][24][25] especially severe asthma. The latter is often characterized by mixed responses of Th2 and Th17 cells and resistant to the steroid therapy.…”
Section: Introductionmentioning
confidence: 99%